The Influence of Product Quality and Brand Image on Repurchase Intention Mediated by Customer Satisfaction on Skintific Skincare Products - I Wayan Ditha Wahyu Pratama; Ida Bagus Teddy Prianthara (GLOBAL HEALTH SCIENCE GROUP, 2025)
Skincare has become an essential part of modern lifestyles as awareness of skin health increases. The beauty industry is rapidly growing, driven by rising demand for skincare products with both aesthetic and health benefits. In Indonesia, this trend is supported by the Zap Index Beauty (2022), which highlights the strong influence of beauty trends on women, contributing significantly to the skincare industry's growth (Sari & Sitompul, 2023). However, consumers often struggle to choose suitable products due to inconsistent information. Skintific is a rapidly growing skincare brand in Indonesia, known for its BPOM-approved, halal-certified products with safe and effective active ingredients (Retnowati, 2024). In a highly competitive market, understanding the factors influencing repurchase intention is crucial. This study analyzes the effects of product quality and brand image on repurchase intention, with consumer satisfaction as a mediating variable, among Skintific users in Badung Regency. Using a quantitative approach, this study employs Partial Least Squares Structural Equation Modeling (PLS-SEM) via SmartPLS 4.0. The sample of 200 respondents was selected through non-probability purposive sampling, referring to Hair et al. (2014), who recommend 100–300 observations for SEM. The findings reveal that product quality and brand image significantly influence consumer satisfaction. Brand image directly affects repurchase intention, while product quality does not. Consumer satisfaction positively influences repurchase intention and mediates the effects of both brand image (β = 0.216; p = 0.002) and product quality (β = 0.162; p = 0.011). These results highlight the importance of consumer satisfaction in strengthening brand image and product quality's impact on repurchase behavior. Firms should focus on improving product quality, building a strong brand image, and enhancing customer experience to foster long-term loyalty.